Nuclear origin of specific yeast mitochondrial aminoacyl-tRNA synthetases. - Schneller, J M (1976)
Hydroxylapatite chromatographies of mitochondrial and total enzymes from a rho+ yeast, or from the related rho degrees mitochondrial DNA-less mutant, show the occurrence in the mitochondrial enzyme of one Phe-, one Met-, one Leu-tRNA synthetase peak which elutes distinctly from the cytoplasmic counterpart and charges well mitochondrial tRNA, whereas the cytoplasmic enzyme does not. The measurement of the mitochondrial synthetases activities in various enzymatic extracts shows that they are not repressed in rho+ cells grown on 10% glucose and that they are concentrated in the mitochondria (Phe- and Met- tRNA synthetases) but are also present outside the mitochondria. It is concluded that yeast mitochondrial protein biosynthesis involves the nuclear coded mitochondrial specific Phe-, Met- and Leu-tRNA synthetases and that the entrance of the synthetases into the mitochondria needs no factor depending on the mitochondrial DNA.